Natural Enemy Abundance in Southeastern Blueberry Agroecosystems: Distance to Edge and Impact of Management Practices. Issue 1 (23rd December 2017) - Whitehouse, T Seth; Sial, Ashfaq A; Schmidt, Jason M
Abstract: Natural enemies are valuable components of agroecosystems as they provide biological control services to help regulate pest populations. Promoting biocontrol services can improve sustainability by decreasing pesticide usage, which is a major challenge for the blueberry industry. Our research is the first to compare natural enemy populations in managed (conventional and organic) and unmanaged blueberry systems, in addition to the effects of non-crop habitat. We conducted our study in 10 blueberry orchards during the growing season across the major blueberry producing counties in Georgia, United States. To estimate the spatial distribution of natural enemies, we conducted suction sampling at three locations in each orchard: within the forested border, along the edge of blueberry orchard adjacent to forested border, and within the interior of the blueberry orchard. Natural enemies maintained higher abundance over the season in unmanaged areas when compared with organic or conventional production systems. In the conventional orchards, natural enemies were more abundant in the surrounding non-crop area compared with the interior of the orchard. Populations were more evenly distributed in less intensive systems (organic and unmanaged). Our results indicate spatial structure in natural enemy populations is related to management practice, and less intensive management can retain higher abundance of natural enemies in blueberry systems. Considerations must be made towards promoting ecologically based management practices to sustain natural enemy populations and potentially increase the delivery of biological control services.